A refuge assured - Green, Jocelyn (Bethany House, a division of Baker Publishing Group, 2018)
"Lacemaker Vivienne Rivard never imagined her craft could threaten her life. Yet in revolutionary France, it is a death sentence when the nobility, and those associated with them, are forced to the guillotine. Vivienne flees to Philadelphia but finds the same dangers lurking in the French Quarter, as revolutionary sympathizers threaten the life of a young boy left in her care, who some suspect to be the Dauphin. Can the French settlement, Azilum, offer permanent refuge? Militiaman Liam Delaney proudly served in the American Revolution, but now that the new government has imposed an oppressive tax that impacts his family, he barely recognizes the democracy he fought for. He wants only to cultivate the land of his hard-won farm near Azilum, but soon finds himself drawn into the escalating tension of the Whiskey Rebellion. When he meets a beautiful young Frenchwoman recently arrived from Paris, they will be drawn together in surprising ways to fight for the peace and safety for which they long."--Back cover.